MDMA Impairs Response to Water Intake in Healthy Volunteers - Matthew J. Baggott; Kathleen J. Garrison; Jeremy R. Coyle; Gantt P. Galloway; Allan J. Barnes; Marilyn A. Huestis; John E. Mendelson (Advances in Pharmacological Sciences)
Hyponatremia is a serious complication of 3,4-methylenedioxymethamphetamine (MDMA) use. We investigated potential mechanisms in two double-blind, placebo-controlled studies. In Study 1, healthy drug-experienced volunteers received MDMA or placebo alone and in combination with the alpha-1 adrenergic inverse agonist prazosin, used as a positive control to release antidiuretic hormone (ADH). In Study 2, volunteers received MDMA or placebo followed by standardized water intake. MDMA lowered serum sodium but did not increase ADH or copeptin, although the control prazosin did increase ADH. Water loading reduced serum sodium more after MDMA than after placebo. There was a trend for women to have lower baseline serum sodium than men, but there were no significant interactions with drug condition. Combining studies, MDMA potentiated the ability of water to lower serum sodium. Thus, hyponatremia appears to be a significant risk when hypotonic fluids are consumed during MDMA use. Clinical trials and events where MDMA use is common should anticipate and mitigate this risk.